2022
DOI: 10.1039/d1fo04267j
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid intervention changes liver Foxp3 methylation and ameliorates the damage caused by Th17/Treg imbalance after long-term alcohol exposure

Abstract: Folic acid, as a key source of methyl donor in DNA methylation, has been proved to play a beneficial role in inflammation modulation, usually impaired in alcoholic liver disease (ALD)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Alcohol consumption is typically accompanied with folic acid deficiency ( 28 ). Our previous study has demonstrated that folic acid supplementation may relieve ethanol-induced Th17/Treg disbalance by altering Foxp3 promoter methylation patterns, which suggest that folic acid may be a feasible preventive strategy for ALD ( 29 ). In this study, in the FA group, histopathological liver changes induced by alcohol were improved, and liver index and the levels of serum ALT, AST, and TG were significantly lower than those in the MOD group.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is typically accompanied with folic acid deficiency ( 28 ). Our previous study has demonstrated that folic acid supplementation may relieve ethanol-induced Th17/Treg disbalance by altering Foxp3 promoter methylation patterns, which suggest that folic acid may be a feasible preventive strategy for ALD ( 29 ). In this study, in the FA group, histopathological liver changes induced by alcohol were improved, and liver index and the levels of serum ALT, AST, and TG were significantly lower than those in the MOD group.…”
Section: Discussionmentioning
confidence: 99%
“…After gently washing twice with PBS (pH7.4) on an ice plate, the single-cell suspension of samples was prepared by PBS (pH7.4) with a concentration of 1 × 10 6 cells/mL. Th17 and Treg were detected as described in our previous procedure . Finally, lymphocytes were detected by the application of a BD FACSAriaIII flow cytometer (BD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Th17 and Treg were detected as described in our previous procedure. 43 Finally, lymphocytes were detected by the application of a BD FACSAriaIII flow cytometer (BD, USA). Data analysis was performed by FlowJo software (BD, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…56,57 FA is a free radical scavenger with a crucial role in this modulation by exerting antioxidant activity essential for nucleotide synthesis, redox state maintenance, and methylation reactions. 14,28,29 Additionally, the influence of FA on the homocysteine (Hcy) levels is notable. Elevated Hcy, a cytotoxic sulfur-containing amino acid, exacerbates oxidative stress 34,58 and is linked to increased dopaminergic neuron depletion in MPTP models.…”
Section: ■ Discussionmentioning
confidence: 99%